2020
DOI: 10.3390/molecules25040823
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Screening Approach to Identify High-Affinity Inhibitors of Serum and Glucocorticoid-Regulated Kinase 1 among Bioactive Natural Products: Combined Molecular Docking and Simulation Studies

Abstract: Serum and glucocorticoid-regulated kinase 1 (SGK1) is a serine/threonine kinase that works under acute transcriptional control by several stimuli, including serum and glucocorticoids. It plays a significant role in the cancer progression and metastasis, as it regulates inflammation, apoptosis, hormone release, neuro-excitability, and cell proliferation. SGK1 has recently been considered as a potential drug target for cancer, diabetes, and neurodegenerative diseases. In the present study, we have performed stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 117 publications
(63 citation statements)
references
References 60 publications
0
63
0
Order By: Relevance
“…In light of the emerging evidence highlighting multiple roles for SGK1 in mediating tumorigenesis and progression, several specific and selective inhibitors of SGK1 have been developed, including GSK650394 ( 49 ), EMD638683 ( 140 ), SI113 ( 141 ), QGY-5-114-A ( 72 ), and ZINC00319000 ( 142 ). The mentioned SGK1 inhibitors and their various anti-tumor effects are summarized in Table 2 .…”
Section: Sgk1 Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In light of the emerging evidence highlighting multiple roles for SGK1 in mediating tumorigenesis and progression, several specific and selective inhibitors of SGK1 have been developed, including GSK650394 ( 49 ), EMD638683 ( 140 ), SI113 ( 141 ), QGY-5-114-A ( 72 ), and ZINC00319000 ( 142 ). The mentioned SGK1 inhibitors and their various anti-tumor effects are summarized in Table 2 .…”
Section: Sgk1 Inhibitorsmentioning
confidence: 99%
“…Using a structure-based virtual high-throughput screening strategy, Mohammad et al ( 142 ) found four compounds bearing appreciable binding affinity and specificity towards the binding pocket of SGK1. Among them, the compound ZINC00319000 was selected and identified based on docking results with all-atom molecular dynamics simulation for 100 ns.…”
Section: Sgk1 Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Poisson-Boltzmann surface area continuum solvation (MM/PBSA) (Fu et al, 2018;Hu et al, 2017;Kumari et al, 2014;Moesgaard et al, 2020;Xue et al, 2018) was also performed to calculate the free binding energy of the ligand. Distance of 3.2 Å was kept as cutoff for bond length for salt bridge and hydrogen bond interactions (Mohammad et al, 2020;. All graphical presentation was prepared using Origin 6.0.…”
Section: Simulations Analysismentioning
confidence: 99%
“…Generally, a protein molecule achieves its function through the collective motion of its atoms, and therefore these atomic motions are widely used to assess the conformational stability of protein-ligand complexes (Mohammad et al, 2020). PCA was performed to reveal the essential and biologically relevant motions from the global trajectories of NSP15 and its drug bound complexes.…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 99%